Can NMR (Nuclear Magnetic Resonance) spectroscopy serve as a diagnostic tool for Rheumatoid Arthritis? - Niraj Kumar Srivastava (Rheumatica Acta: Open Access - Peertechz Publications, 2019)
Rheumatoid arthritis (RA) is a general, chronic, systemic and autoimmune inflammatory disease. This disease represents the inflammatory response of the synovium resulting to hyperplasia of synovial cells along with associated destruction of cartilage, bone and ligaments, eventually leading to deformity of the joints. There is a considerable alteration observed in the metabolism. Chronic inflammation is responsible for altering the metabolism and also the metabolic profile of an individual patient with early inflammatory arthritis expects the following route of disease. These metabolic changes would identify biomarkers, which may be useful for the diagnostic purposes. NMR (nuclear magnetic resonance) spectroscopy based metabolomics studies of serum, urine and synovial fluid of RA were performed. These studies reflected the possibility of the development of metabolomics based diagnostic methods for RA. So, our question "Can NMR (Nuclear Magnetic Resonance) spectroscopy serve as a diagnostic tool for rheumatoid arthritis?" will definitely get an answer with the development of NMR based diagnostic method for RA.